Mode of Delivery in Premature Neonates: Does It Matter? - Diana A. Racusin; Kathleen M. Antony; Jennifer Haase; Melissa Bondy; Kjersti M. Aagaard (Thieme Medical Publishers, Inc., 2016)
Abstract Objective Despite the current prevalence of preterm births, no clear guidelines exist on the optimal mode of delivery. Our objective was to investigate the effects of mode of delivery on neonatal outcomes among premature infants in a large cohort. Study Design We applied a retrospective cohort study design to a database of 6,408 births. Neonates were stratified by birth weight and a composite score was calculated to assess neonatal outcomes. The results were then further stratified by fetal exposure to antenatal steroids, birth weight, and mode of delivery. Results No improvement in neonatal outcome with cesarean delivery (CD) was noted when subjects were stratified by mode of delivery, both in the presence or absence of antenatal corticosteroid administration. In the 1,500 to 1,999 g subgroup, there appears to be an increased risk of respiratory distress syndromes in neonates born by CD. Conclusion In our all-comers cohort, replicative of everyday obstetric practice, CD did not improve neonatal outcomes in preterm infants.